IMAM MENGHADIRKAN KRISTUS DALAM GEREJA MELALUI KEPEMIMPINAN MANAJERIAL PAROKIAL Studi Kepemimpinan Pastor Paroki di Paroki Trinitas Cengkareng Masa Bakti 2011-2014 - Aloysius Wahyu Nugroho (Jurnal Teologi (Journal of Theology), 2014)
The fruitfulness of pastoral care to the faithful in the parishes is influenced by several factors. One important factor is the managerial leadership of the parish priest, given that he stands at the center of the organization as leader and manager of a parish. This article discusses a study that focuses on the management of pastoral care that affects the fruitfulness of pastoral care in the Trinity Parish in Cengkareng, Jakarta. The results of this study answers the question of how planning, organizing, leading, and controlling affect the leadership of the parish priest and the fruitfulness of pastoral ministry. In this study the identity of the parish priest as displayed through parochial managerial leadership is also questioned. From the research it is concluded that managerial leadership of parish priest gives a considerable contribution to the fruitfulness of pastoral care to the parishioners.